China's growth and the middle income trap in Latin America - Valdiglesias Oviedo, Jhon (2024)
The main objective of this article is to identify the factors explaining disparities in GDP per capita between Latin American economies and the economy of China, particularly considering the remarkable economic growth of the latter contrasted with the stagnation experienced by Latin American countries, which are trapped in what is known as the "middle-income trap." To achieve this objective, an econometric model is employed using the panel data method, primarily utilizing development indicators available in the World Bank database. The results obtained reveal that institutional quality constitutes a determining factor in the economic disparities between the mentioned economies, highlighting the institutional improvements observed in China in recent years. As a result of our conclusions, it is recommended that Latin American countries consider implementing institutional strategies similar to those that have enabled China to break free from the "middle-income trap."